Tetracycline removal from aqueous solution through photo-anodic oxidation process using rotating graphite cylinder anode - Uonis, Heba F.; Abbar, Ali H.; Kandemirli, Fatma (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
In the present work, tetracycline (TC) was removed from a simulated wastewater through a new photo-anodic oxidation process with a rotating graphite cylinder anode. The effects of current density, pH, rotation speed, and NaCl addition were evaluated. The results confirmed that increasing the current density results in improving the removal of TC. However, increasing the current density beyond 5 mA/cm2 had little effect on TC removal. Results revealed that TC removal using photoanodic oxidation can be achieved at high performance with an initial pH of 5. Increasing or decreasing pH beyond this value has a negative effect on TC removal. Increasing rotation speed gave better performance for TC removal due to the increase in mass transfer. The addition of NaCl improved the removal efficiency of TC due to the participation of indirect anodic oxidation within the oxidation process. The best conditions were: current density of 5mA/cm2, pH=5, 250 rpm, and the addition of 1 g/L NaCl, in which TC removal of 84% was achieved that claims (103 kWh/m3) as a total electrical energy consumption. In comparison with the anodic oxidation process alone, photo-anodic improved TC removal by an increment of (13.73%), confirming the photo-anodic process can be adopted successfully for treating wastewaters.